Spinal loading and lift style in confined vertical space - Weston, Eric B.; Dufour, Jonathan S.; Lu, Ming-Lun; Marras, William S. (Applied ergonomics, 2020)
The objective of this study was to investigate biomechanical loads on the lumbar spine as a function of working in a confined vertical space, consistent with baggage handling inside the baggage compartment of an airplane. Ten male subjects performed baggage handling tasks using confined (kneeling, sitting) and unconfined (stooping) lifting styles. Dependent measures of torso flexion and three-dimensional spinal loads were assessed with an electromyography-driven biomechanical model. Lifting exertions typical to airline baggage handling posed significant risk to the lumbar spine, regardless of lifting style. Statistically significant differences attributable to lift style (stooping, kneeling, sitting) were not observed for peak compressive, lateral shear, or resultant spinal loads, but lifting while kneeling decreased anterior/posterior (A/P) shear spinal loads relative to stooping (p = 0.02). Collectively, kneeling offers the greatest benefit when lifting in confined spaces because of the ability to keep the torso upright, subsequently reducing shear forces on the lumbar spine. •Little prior biomechanical research has evaluated varied lifting styles (kneeling, sitting) in confined vertical space.•Baggage handling tasks performed in confined vertical space pose a high low back injury risk, regardless of lift style.•From a low back loading perspective, kneeling is preferable to sitting when lifting in confined vertical space.